Redes de alimentos y producción artesanal en la parroquia Saraguro, cantón Saraguro :Un aporte al análisis de la soberanía alimentaria - Sigcho Poma, Pedro Manuel (2015)
This research aims to contribute to the systematization of experiences of supply networks and craft production, in a context of strengthening indigenous and peasant communities of Saraguro parish. This means describe the type of products that are being cultivated to ensure food sovereignty of communities and families know the values and cultural principles that still exist in indigenous and peasant communities that are contributing to Sumak Kawsay Saraguro village, but also means analyzing if in the Saraguro parish is potencializando popular and solidarity economy, if farmers have a say in what they grow, whether family production units contribute to environmental, social and economic sustainability. After knowing the potential of food production, we can meet the parish and its thirteen communities that way being processed agricultural and livestock products, which are the most important crops in the parish are. It is also important to know and define supply networks, marketing, trade, processing and consumption of food, the population has been maintaining traditional and ancestral way under the principles of equity, reciprocity and solidarity in most communities have with similarities cultural values, although changes in eating habits, migration of youth demonstrates the loss of local values. Under the annotated principles, rural communities of Saraguro parish still have not been studied in order to determine the importance within networks of food sovereignty.